2021
DOI: 10.3390/nu13113897
|View full text |Cite
|
Sign up to set email alerts
|

Water Kefir and Derived Pasteurized Beverages Modulate Gut Microbiota, Intestinal Permeability and Cytokine Production In Vitro

Abstract: Fermentation is an ancient food preservation process, and fermented products have been traditionally consumed in different cultures worldwide over the years. The interplay between human gut microbiota, diet and host health is widely recognized. Diet is one of the main factors modulating gut microbiota potentially with beneficial effects on human health. Fermented dairy products have received much attention, but other sources of probiotic delivery through food received far less attention. In this research, a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…Research has indicated that pasteurized fermented milk enhances intestinal microbial composition, promotes the production of anti-inflammatory factors IL-10 and IL-1β, and mitigates inflammation-induced intestinal epithelial barrier disruption . Similarly, studies have shown that heat-treated camel milk (72 °C for 2 min) alleviates gut barrier damage associated with psychological stress in mice .…”
Section: The Guardian Effect Of Milk Ingredients On the Gut Barriermentioning
confidence: 99%
“…Research has indicated that pasteurized fermented milk enhances intestinal microbial composition, promotes the production of anti-inflammatory factors IL-10 and IL-1β, and mitigates inflammation-induced intestinal epithelial barrier disruption . Similarly, studies have shown that heat-treated camel milk (72 °C for 2 min) alleviates gut barrier damage associated with psychological stress in mice .…”
Section: The Guardian Effect Of Milk Ingredients On the Gut Barriermentioning
confidence: 99%
“…Microbial processes on cereals such as fermentation also affect the improvement of protein digestibility and the reduction in allergens with microbial proteases [45,46]. Moreover, water kefir increased beneficial short-chain fatty acid production at the microbial level, reduced detrimental proteolytic fermentation compounds, and increased Bifidobacterium genus abundance [47]. Vegetables and fruits are also used in the production of nondairy probiotic products.…”
Section: Streptococcus Streptococcus Thermophilesmentioning
confidence: 99%
“…Many probiotic bacteria have been shown to help ameliorate type 2 diabetes disorder through various means such as reducing insulin resistance and improving glucose homeostasis [40]. Short-chain fatty acids (SCFAs) such as acetate, propionate, and butyrate have been shown to be important targets in the treatment of type 2 diabetes [41], which has also been reported in kefir [31], showing positive colonic and immune modulation [42]. The MK-9 variant of menaquinone (Vitamin K 2 ) has been detected in kefir [43], which plays a role in improving insulin resistance and reducing type 2 diabetes by means of its anti-inflammatory and lipid-lowering effects [44].…”
Section: Hypoglycemic Properties Of Kefirmentioning
confidence: 99%